The non-lemniscal auditory cortex in ferrets: Convergence of corticotectal inputs in the superior colliculus - Bajo, V; Nodal, F; Bizley, J; King, A (2010)
Descending cortical inputs to the superior colliculus (SC) contribute to the unisensory response properties of the neurons found there and are critical for multisensory integration. However, little is known about the relative contribution of different auditory cortical areas to this projection or the distribution of their terminals in the SC. We characterized this projection in the ferret by injecting tracers in the SC and auditory cortex. Large pyramidal neurons were labeled in layer V of different parts of the ectosylvian gyrus after tracer injections in the SC. Those cells were most numerous in the anterior ectosylvian gyrus (AEG), and particularly in the anterior ventral field, which receives both auditory and visual inputs. Labeling was also found in the posterior ectosylvian gyrus (PEG), predominantly in the tonotopically organized posterior suprasylvian field. Profuse anterograde labeling was present in the SC following tracer injections at the site of acoustically responsive neurons in the AEG or PEG, with terminal fields being both more prominent and clustered for inputs originating from the AEG. Terminals from both cortical areas were located throughout the intermediate and deep layers, but were most concentrated in the posterior half of the SC, where peripheral stimulus locations are represented. No inputs were identified from primary auditory cortical areas, although some labeling was found in the surrounding sulci. Our findings suggest that higher level auditory cortical areas, including those involved in multisensory processing, may modulate SC function via their projections into its deeper layers. © 2010 Bajo, Nodal, Bizley and King.